1993
DOI: 10.1302/0301-620x.75b5.8376444
|View full text |Cite
|
Sign up to set email alerts
|

Torsional deformity after intramedullary nailing of femoral shaft fractures. Measurement of anteversion angles in 110 patients

Abstract: The torsion of both femora was evaluated in 110 patients who had been treated by intramedullary nailing for unilateral femoral shaft fractures. The anteversion (AV) angle was measured by ultrasound, using a tilted-transducer technique. True torsional deformity, defined as an AV difference of 15#{176} or more between sides was found in 21 patients, but only eight had complaints related to the deformity. Three patients had reoperations for troublesome external torsional deformities. Of 26 patients with AV differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
1
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(109 citation statements)
references
References 0 publications
2
99
1
7
Order By: Relevance
“…Ipsilateral nailing of femoral and tibial shafts increases the risk of malunion, rotatory instability due to shortening, and axis defects [13]. Braten et al [14] and Sojbjerg et al [15] found this complication in 40% and 25% of cases respectively, but for Braten et al in only 10% were the fractures to blame. The systematic use of locking screws did not prevent this problem: it is during intervention that the rotation error is established.…”
Section: Discussionmentioning
confidence: 99%
“…Ipsilateral nailing of femoral and tibial shafts increases the risk of malunion, rotatory instability due to shortening, and axis defects [13]. Braten et al [14] and Sojbjerg et al [15] found this complication in 40% and 25% of cases respectively, but for Braten et al in only 10% were the fractures to blame. The systematic use of locking screws did not prevent this problem: it is during intervention that the rotation error is established.…”
Section: Discussionmentioning
confidence: 99%
“…Angular (coronal and sagital) deformity of ≥5º and rotational deformity of ≥15º were considered unacceptable. 9,10 Malunion in the 4 patients was unacceptable; they had varus/valgus angulation of 10º to 25º, flexion/extension of 5º to 15º, and rotational deformities of 5º to 25º. All patients had deformed, shortened, and wasted lower limbs, with knee stiffness.…”
Section: Recordsmentioning
confidence: 99%
“…21,22 Although ultrasound is believed to be more consistent it cannot be widely used because it is predominantly observer dependent. 8,12 Computed tomography is currently the method of choice because of its reliability and reproducibility to determine rotational malalignment. [23][24][25] Ante version differences less than 10° are normal variations.…”
Section: Resultsmentioning
confidence: 99%
“…Since the possible torsion of a locked femoral nail itself is too small to be the cause of rotational malalignment the deformity is established during the operation, indicating inadequate reduction of the fracture. [11][12][13][14] The rotational malalignment is detected and corrected intraoperatively by techniques like comparing the lesser trochanter profile of the uninjured limb,"cortical step sign" and diameter difference sign. [15][16][17][18] Rotational malalignment or torsional deformity is expressed as a difference in femoral ante version between the injured and uninjured leg and loss of rotational movements.…”
Section: Introductionmentioning
confidence: 99%